2021
DOI: 10.3847/1538-3881/abda53
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Spectra and Multiwavelength Machine Learning Classification for Likely Counterparts to Fermi 3FGL Unassociated Sources

Abstract: We conduct X-ray spectral fits on 184 likely counterparts to Fermi-LAT 3FGL unassociated sources. Characterization and classification of these sources allows for more complete population studies of the high-energy sky. Most of these X-ray spectra are well fit by an absorbed power-law model, as expected for a population dominated by blazars and pulsars. A small subset of seven X-ray sources have spectra unlike the power law expected from a blazar or pulsar and may be linked to coincident stars or background emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Three of the X-ray sources they analyzed had plausible optical counterparts, and two of these are present within the 4FGL 95% confidence ellipse (see Figure 1; we note these are the same two sources identified by Hui et al (2015) from the Swift data). As pointed out by Salvetti et al (2017), the fainter of these two X-ray sources is a known galaxy, and is unlikely to be the source of the γ-ray emission, especially given the highly curved γ-ray spectrum; Kerby et al (2021) estimate the probability that this 4FGL source is a blazar is only ∼3%, supporting the inference that the fainter X-ray source is unrelated to the γ-ray emission.…”
Section: Xmmmentioning
confidence: 74%
See 2 more Smart Citations
“…Three of the X-ray sources they analyzed had plausible optical counterparts, and two of these are present within the 4FGL 95% confidence ellipse (see Figure 1; we note these are the same two sources identified by Hui et al (2015) from the Swift data). As pointed out by Salvetti et al (2017), the fainter of these two X-ray sources is a known galaxy, and is unlikely to be the source of the γ-ray emission, especially given the highly curved γ-ray spectrum; Kerby et al (2021) estimate the probability that this 4FGL source is a blazar is only ∼3%, supporting the inference that the fainter X-ray source is unrelated to the γ-ray emission.…”
Section: Xmmmentioning
confidence: 74%
“…No spectral or temporal analysis of these data was carried out by this group. Kerby et al (2021) performed a more detailed spectral analysis of this source, finding a best fit power law index of Γ = 1.89 +0.18 −0.17 and unabsorbed 0.3-10 keV flux of (7.9 +1.2 −1.0 ) × 10 −14 erg cm -2 s -1 . It is notable that despite using the same datasets, these two flux estimates do not agree within the uncertainties.…”
Section: Swiftmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate HH219 in more detail as a potential source of the gamma-ray emission from 4FGL J0822.8-4207, we submitted a Target of Opportunity request to the Niel Gehrels Swift Observatory (henceforth Swift). Observations with Swift are a powerful tool for localizing high-energy emission from Fermi-LAT sources by using the Swift X-ray Telescope (Swift-XRT, Burrows et al 2005) to observe 0.3−10.0 keV X-rays (for example, the ongoing Swift follow-up program described in Kerby et al 2021). As many sources of gamma rays observed with Fermi also produce X-rays via synchrotron emission, if HH219 is producing gamma-ray emission by leptonic processes, it may produce characteristic X-rays as well.…”
Section: Swift-xrt Datamentioning
confidence: 99%
“…From their initial list, 31 sources from the 3FGL unassociated list defied categorization and were labeled 'ambiguous'. Recent work by this collaboration (Kerby et al 2021) continued that analysis by including more detailed X-ray spectral fitting and systematically adding spectral parameters to machine learning. Adding UV-visual observations from the Swift-UVOT telescope is particularly useful, as pulsars are usually extremely dim in the UV-visual range Saz Parkinson et al 2016) while blazars emit at all wavelengths and at low redshift can be observed across the electromagnetic spectrum (Ghisellini & Tavecchio 2008).…”
mentioning
confidence: 99%